Differences in occupational health and safety efforts between adopters and non-adopters of certified occupational health and safety management systems. (August 2022) - Uhrenholdt Madsen, Christian; Vester Thorsen, Sannie; Hasle, Peter; Leonhardt Laursen, Line; Dyreborg, Johnny
Highlights: A survey of 4, 202 Danish workplaces compares OHS efforts of adopters and non-adopters of Certified OHS Management Systems (COHSMSs). Two main dimensions of the OHS efforts are evaluated: the 'systematic process-related' OHS efforts and the 'content-related' OHS efforts. Adopters of COHSMSs have a higher overall level of both systematic process-related OHS efforts and content-related OHS efforts, compared to non-adopters. The study therefore supports the assumption that COHSMS adopters generally perform a higher level of OHS management than non-adopters do. Abstract: Certified occupational health and safety management systems (COHSMSs) continue to grow in popularity and to diffuse to new industries. This study investigated differences in occupational health and safety efforts between adopters and non-adopters of COHSMSs. We used cross-sectional survey data from 4, 202 Danish workplaces from all sectors to compare self-reported occupational health and safety efforts in workplaces with a COHSMS and workplaces without a COHSMS. The 'systematic process-related OHS efforts' and 'content-related OHS efforts' were scored on five and seven scales, respectively, for both adopters and non-adopters. The results of linear regression analysis revealed significantly lower score values for non-adopters than for adopters of COHSMSs, which means certified workplaces perform better than non-certified workplaces in both process-related and content-related OHS activities. We conclude that COHSMSs workplaces have a higher overall level of efforts for both process and content OHS activities. The study therefore supports the assumption that COHSMS adopters provide a higher level of OHS management than non-adopters, and that using the company's OHS performance as merely 'window dressing' is not a general feature of adopters. However, the results also indicate that a small group of COHSMS adopters has a considerably lower level of OHS effort than non-adopters, which implies that the certification system does not necessarily secure a high level of OHS management for all adopters. Furthermore, a small group of adopters have high process activities and low content activities, suggesting a decoupling between the systematic OHS processes and the specific preventive activities in the workplace, which could be a sign of window dressing. Further research is needed to establish the possible effects on health and safety outcomes, such as lost-time injuries.